2013
DOI: 10.4028/www.scientific.net/amm.315.830
|View full text |Cite
|
Sign up to set email alerts
|

Load Capacity of Partially Textured Journal Bearing with Trapezoidal Recess

Abstract: This work presents the load carrying capacity of partially textured journal bearing with trapezoidal recess. The partial texture geometry is composed of a number of successive cells of trapezoidal recess and land configurations. The non-dimensional pressure expressions for the partially textured journal bearing with trapezoidal recess are derived. Results of nondimensional load capacity are provided taking into consideration of texture geometry with trapezoidal recess and extent of partial texture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Researchers [12][13][14][15][16][17] experimentally and theoretically studied the influence of rectangular dimples on the bearing performance. Rao et al 18 concluded that partial texturing utilizing trapezoidal surface textures can improve the load-bearing ability of journal bearings. Meng et al 19 showed that compound dimples can enhance the load-bearing ability and reduce the friction vis-a-vis rectangular-shaped dimple on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers [12][13][14][15][16][17] experimentally and theoretically studied the influence of rectangular dimples on the bearing performance. Rao et al 18 concluded that partial texturing utilizing trapezoidal surface textures can improve the load-bearing ability of journal bearings. Meng et al 19 showed that compound dimples can enhance the load-bearing ability and reduce the friction vis-a-vis rectangular-shaped dimple on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various other surface texture geometries have been adopted by different researchers. Tala-Ighil et al 9 used elliptical surface geometry of dimple and Rao et al 10 used trapezoidal surface texturing geometry and showed that the load capacity of concentric journal bearing can be enhanced using partially textured bearing surface. Meng et al 11 made a comparative study on compound (rectangular-spherical dimples) and simple dimple (rectangular dimples), using fluid structure interaction, analyzing the performance of a journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…9 used elliptical surface geometry of dimple and Rao et al. 10 used trapezoidal surface texturing geometry and showed that the load capacity of concentric journal bearing can be enhanced using partially textured bearing surface. Meng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al. 31 utilized the trapezoidal shaped texture and concluded that partial texturing can enhance the load-carrying capacity of journal bearing system. Meng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the bearing temperature and dynamic bearing coefficients are affected by surface texturing. Rao et al 31 utilized the trapezoidal shaped texture and concluded that partial texturing can enhance the load-carrying capacity of journal bearing system. Meng et al 32 studied the effect of compound dimple/texture on the performance of journal bearing and concluded that compound dimple on the bearing surface provides better load-carrying capacity and reduction in friction than simple rectangular dimple.…”
Section: Introductionmentioning
confidence: 99%